2022
DOI: 10.1002/ppul.26068
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in school‐aged children with asthma during the Covid‐19 pandemic

Abstract: Introduction The coronavirus 2019 disease (Covid‐19) pandemic led to a number of measures being introduced in many countries worldwide. Lockdowns were imposed on individuals aged <18 years, education was delivered online, and mask‐wearing was made compulsory in public places, resulting in an unprecedented period for children. Real‐life data showing how children with asthma are affected by major changes are limited. This study investigated how asthmatic children are affected by pandemic conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…31 In the case of hospitalizations, the findings were also consistent across all three included studies that examined this endpoint. 31,42,47 More specifically, the study by Sun et al, reported a significant reduction of 76% in the absolute number of hospitalizations for asthma during the lockdown compared to the prelockdown period, while a reduction was also observed in the study by Akelma et al, although the difference in the absolute number of hospitalizations between the two follow-up periods was not statistically significant. Papadopoulos et al reported a prelockdown proportion of patients requiring hospitalization for asthma equal to 13.1%, which fell to 2.0% during the lockdown period, with this reduction being statistically significant.…”
Section: Ed Visits Hospitalizations and Other Endpointsmentioning
confidence: 88%
See 3 more Smart Citations
“…31 In the case of hospitalizations, the findings were also consistent across all three included studies that examined this endpoint. 31,42,47 More specifically, the study by Sun et al, reported a significant reduction of 76% in the absolute number of hospitalizations for asthma during the lockdown compared to the prelockdown period, while a reduction was also observed in the study by Akelma et al, although the difference in the absolute number of hospitalizations between the two follow-up periods was not statistically significant. Papadopoulos et al reported a prelockdown proportion of patients requiring hospitalization for asthma equal to 13.1%, which fell to 2.0% during the lockdown period, with this reduction being statistically significant.…”
Section: Ed Visits Hospitalizations and Other Endpointsmentioning
confidence: 88%
“…In addition, four studies reported changes in the proportion of patients characterized by well-controlled asthma, 39,40,43,47 while five studies reported changes in the proportion of patients characterized by poorly controlled asthma. 42,43,45,47,48 The pooled proportion of patients with wellcontrolled asthma increased during the lockdown period (Supporting Information: Figure 1) and the pooled RR was 1.35 (95% CI: 1.06, 1.71, I 2 : 77.6%) (Figure 3). At the other end, the pooled proportion of patients with poorly controlled asthma decreased during the lockdown period (Supporting Information: Figure 2) and the pooled RR was 0.47 (95% CI: 0.38, 0.57, I 2 : 0.0%) (Figure 4).…”
Section: Asthma Symptoms Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…While we also observed a similar spike involving SABA, there are limited literature quantifying asthma rescue medication use early in the COVID-19 pandemic. Instead, most literature on asthma rescue medication like SABA involved longer COVID-19 pandemic periods with little comparisons on usage between the early and later parts of the pandemic [29][30][31]. These authors found an overall decreased use of SABA during COVID-19.…”
Section: Plos Onementioning
confidence: 99%